ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF PADA IBU USIA DI BAWAH 20 TAHUN - UMU CHABIBAH HEMI RISTIANA; KISWATI KISWATI; ENY SENDRA; RIRIN INDRIANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The global rate of teenage pregnancy is still high, at 41/1000 women. In Indonesia, approximately 7% of women aged 15 - 19 have given birth or are currently pregnant with their first child. It has impact on the low rate (48,8%) of exclusive breastfeeding among mothers aged under 20 years. That is possibly related to several factors. The purpose of this research was to determine the factors associated with exclusive breastfeeding of mothers aged under 20 years. This research used a traditional review design to conducted a literature review which the literature is scientific articles, both national and international, that are relevant to the research topic. The articles were found using the keywords (